Impact of storage systems on grain microflora, quality and viability of paddy during storage - RAO, V. KRISHNA (Indian Phytopathology, 2002)
The effect of existing storage structures, viz., cement bin, Kotlu, Puri and Steel bin of farmers on grain micro flora, quality and viability of paddy seeds during storage at one of the humid regions of Krishna- Godavari zone (A P) was studied. The results indicated that the paddy stored in cement bin followed by steel bin and Kotlu recorded high incidence of fungi, bacteria, discoloured grains and high moisture content. The paddy stored in cement bin completely lost viability within 90 days of storage. Puri was found to be the best storage structure recording high germination percentage with low incidence of fungi, bacteria, discoloured grains and low moisture content.